White Paper - Open Science in a Digital Republic - Scientific and Technical Information Department - CNRS (OpenEdition Press, 2016)
At a time when the Digital Republic Bill is proposing to insert provisions relating to open access in the French Research Code, the French National Centre for Scientific Research (CNRS), alongside its partners in the ISTEX project, as well as a large number of researchers and actors in the field of public research, are offering via this White Paper the results of their deliberations and analyses.For several years now, the scientific community involved in public research has been arguing for t...